2008
DOI: 10.1248/bpb.31.1067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metabolites of the Lignans Enterolactone and Enterodiol on Osteoblastic Differentiation of MG-63 Cells

Abstract: The role of estrogens and estrogen-like molecules in regulating bone cell activities is central to understanding the etiology and treatment of postmenopausal osteoporosis. 1,2) In the past few years, natural estrogen-like molecules, the phytoestrogens, have attracted attention for their potential roles in osteoporosis prevention and treatment. 3) In contrast to the isoflavone-type phytoestrogens such as genistein, lignan-type phytoestrogens have rarely been studied, although they are widely distributed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Epidemiological and pharmacological studies reveal that END and its oxidation product ENL, in particular, afford protection against osteoporosis, cardiovascular diseases, hyperlipidemia, breast cancer, colon cancer, prostate cancer and menopausal syndrome (Adlercreutz, 2007;Feng, Shi, & Ye, 2008;Adolphe, Whiting, Juurlink, Thorpe & Alcom, 2010;Ayella et al, 2010;Zaineddin et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and pharmacological studies reveal that END and its oxidation product ENL, in particular, afford protection against osteoporosis, cardiovascular diseases, hyperlipidemia, breast cancer, colon cancer, prostate cancer and menopausal syndrome (Adlercreutz, 2007;Feng, Shi, & Ye, 2008;Adolphe, Whiting, Juurlink, Thorpe & Alcom, 2010;Ayella et al, 2010;Zaineddin et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 7 d of incubation with doses as low as 0.01 mg/ml of enterolactone and enterodiol increased mRNA expression of osteonectin and type I collagen in the MG-63 human osteosarcoma cell line, which is a human osteoblastlike cell line (Feng et al, 2008). Human and animal data showed that FS oil or a high ALA diet can result in lower levels of serum tumour necrosis factor-a and prostaglandin E2 in bone (Griel et al, 2007;Mollard et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…When consumed, the ALA in FS may be metabolized in small amounts into longer chain metabolites, eicosapentaenoic acid and docosahexaenoic acid, compounds that have been shown to inhibit bone loss (Plourde & Cunnane, 2007;Sakaguchi et al, 1994;Watkins et al, 2006). Similarly, SDG is metabolized into lignan metabolites, enterodiol and enterolactone (Thompson et al, 1991), compounds that were also found to modulate bone metabolism and be positively associated with BMD (Feng et al, 2008;Kim et al, 2002).…”
mentioning
confidence: 99%
“…Using in vitro models, the mammalian lignans and ALA have been shown to exert direct effects on bone cells by modulating cell viability, DNA content, alkaline phosphatase activity, and gene expression of markers of bone formation, including osteonectin and type I collagen (Table 21.5) (Fujimori et al 1989;Feng et al 2008). Due to the estrogenic/antiestrogenic potential of the lignans, as well as the ability for the n-3 PUFA to modulate bone metabolism, research interest on the action of FS on bone health has expanded in recent years.…”
Section: Flaxseed Flaxseed Lignan Flaxseed Oil and Bone Metabolismmentioning
confidence: 99%